Systematic research is needed on the potential effects of lifelong technology experience on cognition: a mini-review and recommendations - Beaudoin, Monique E.; Jones, Kelly M.; Jerome, Bernadette; Martinez, David; George, Tim; Pandža, Nick B. (Frontiers in Psychology, 2024)
Digital technology now occupies a fundamental space in human life. Increasingly sophisticated access to information and social interactions has enabled a sort of offloading of many aspects of cognition, and for many people, this technology use has been lifelong. While the global development of technologies advances exponentially as part of the Fourth Industrial Revolution, researchers have not yet fully characterized the human effects of this technology-centric revolution at the same pace. In this mini-review, we consider three important higher-level cognitive functions: creativity, adaptability, and decision-making, and discuss their potential relationship to lifelong digital technology experience, which here includes both passive exposure and active use of electronic devices. We then articulate the gaps in related literature and knowledge, and outline general considerations, suggestions, and challenges for future research avenues. In general, we found that prior research has investigated uses of specific technology products on lower-level cognition (e.g., how does the use of online search engines affect memory?), but there is a lack of research assessing the overall effects of technology experience on cognitive functioning, particularly complex cognition.